A Retrospective Study on Diagnosing Efficacy of Transvaginal Sonography Versus Hysteroscopy in Abnormal Uterine Bleeding - Chaudhary, Dr. Priyanka; Singh, Dr. Poonam; Najam, Dr Rehana; Shrivastava, Dr Shubhra; Lalwani, Dr Astha (International Journal of Innovative Research in Medical Science, 2022)
Background: Around 33% of females that presents to gynecological OPD have abnormal uterine bleeding (AUB). Out of various causes of AUB, the most common causes that were encountered includes endometrial polyps & hyperplasia, leiomyomas and annovulation. By diagnosing the etiology of abnormal uterine bleeding accurately, the prevalence of hysterectomies can be reduced. So, in this study the effectiveness of transvaginal sonography versus hysteroscopy was compared in the diagnosis of AUB. Methods: A total number of 64 patients in perimenopausal age group with AUB were enrolled in the study. All the patients were subjected to TVS & Hysteroscopy for the assessment of uterine cavity which was followed by endometrial sampling and then the sensitivity & specificity of both the modalities were statistically analysed. Results: In our study, mostly patients were presented with heavy menstrual bleeding(n=26) followed by frequent bleeding, intermenstrual bleeding & irregular menstrual bleeding. On TVS, 12 patients had normal uterine cavity, adenomyosis,fibroids, polyp, cystic ovaries were seen in 19,18,10, & 5, in women with AUB .On Hysteroscopy, uterine cavity was found normal in 15 females followed by endometrial polyp, fibroids & cerebroid appearance was seen in, 12, 12, 4 patients respectively and on histopathology, endometrial hyperplasia (n=20)was most commonly seen followed by polyp, proliferative & secretory endometrium. Both TVS & Hysteroscopy findings were statiscally significant. Conclusion: Both Hysteroscopy & transvaginal sonography has the ability to determine the abnormalities of endometrium with different accuracy. Hence the patients who were presented with AUB should undergone TVS as primary measure, followed by hysteroscopy in the same sitting for diagnostic & therapeutic procedure whenever required.